Experiment and Analysis of Car Alternator for Wind Turbine Application - Pudji Irasari (National Research and Innovation Agency, 2011)
This paper discusses experiment and analysis to find out the feasibility of a car alternator to be used as a generator for wind turbine. The experiment was conducted twice. The first experiment was to characterize the alternator to determine the mechanical transmission ratio. In this experiment the alternator was driven by a lathe machine and its output power was supplied to charge a battery. In the second experiment the alternator was integrated with the turbine blades and they were tested as a unit system. In both experiments, the electric generation of alternator was executed with fixed excitation current method. The correlation between the alternator characteristic and the tip speed ratio gives the mechanical transmission ratio of 1 : 3. The experiment results show that the efficiency of alternator is around 50% and cut-in wind speed (after correction) is 6.35 m/s indicating that alternator is not feasible for wind turbine system application.